Screening for Musculoskeletal Deviations: Epidemiology and Patterns of Occurrence among Basic School Pupils in Accra Ghana - , Ajediran I. Bello; , Anna Hughton; , Josephine Ahenkorah; , Samuel Otoo; , Beatrice Sankar (Archives of Current Research International, 2016)
Background: Childhood age through adolescence mark period of major postural transformation which warrants screening for structural abnormalities. The study provided needs assessment for musculoskeletal screening and determined the prevalence of musculoskeletal deviations (MSDs) among pupils in Junior High Schools. Methods: An all-inclusive qualitative musculoskeletal screening exercise was conducted in eight private and public basic schools within Accra Metropolis. The schools were sampled through multi-staged sampling technique from a cluster of 264 schools. After due permissions from the Ghana Education Service Directorate, Head Teachers and parents, pupils were screened for various MSDs. Screening procedures largely involved manual testing, observation and measurements using paediatric Gait, Arms, Legs and Spine (pGALS) as a guide. Data were gleaned to descriptive and inferential analysis at 95% CI. Results: A total of 1,532 pupils (mean age: 14.6±1.7 years) were screened. They comprised 696 (45.3%) males. The pattern of MSDs indicate Hallux valgus as the most presented MSDs, 475 (31%) and 242 (15.8%) of them were females. Elevated scapular was the least as found among 21 (1.3%) pupils. There were significant differences (p<0.05) in the frequency of male and female pupils with clawed toes, genu valgus, winged scapular, kyphosis, scoliosis and cubital valgus. Two Hundred and Fifty-Four (16.6%) of the total sampled pupils presented with two or more MSDs. Conclusion: The outcome of the screening revealed high prevalence of MSDs among the sampled pupils with females being more predisposed than their male counterparts. The finding has provided cue for initiating musculoskeletal screening among Ghanaian children in basic schools.